Test-retest and intrasession reliability of assisted sprint outcome measurements using a motorized resistance device - Eriksrud, O.; Westheim, F. (Frontiers in Sports and Active Living, 2025)
The aim of this study was to determine reliability of assisted sprint outcome measurements using a motorized resistance device (MRD). A total of 21 participants (16 males and 5 females; age 22.3 ± 3.9 years, body mass 75.2 ± 6.9 kg, height 177.9 ± 6.8 cm) completed two assisted sprint tests on four different test sessions while exposed to an external load (3 kg) provided by the MRD. Outcome variables included time, top speed, maximum acceleration and 5 m split times and speeds. Intrasession and test-retest reliability was assessed using intraclass correlation coefficient (ICC), coefficient of variation (CV), typical error (TE), smallest worthwhile (SWC) and moderate worthwhile change (MDC). For test-retest reliability mostly high to extremely high ICC values (>0.77), and good (<5%) CV values were observed for all outcome measurements. Specifically, all outcome measurements showed high to extremely high relative reliability (ICC = 0.95) except 0-5 m time (0.86) and maximum acceleration (0.77). Good absolute reliability was observed for all outcome measurements (CV range: 0.9-3.7) except maximum acceleration (8.7). Furthermore, most outcome variables were rated as good and ok for SWC. Similar findings were observed for intrasession reliability with very high ICC values for all outcome measurements except maximum acceleration (0.85-0.93) and 0-5 time for session 2-4 (0.88-0.92). Similarly, CV was good for all outcome measurements for all sessions except maximum acceleration (5.7-5.9%). In addition, all outcome measurements had good to ok SWC, except for maximum acceleration. In conclusion, the present study shows that the MRD can obtain reliable assisted sprint outcome measurements and thereby provide coaches and researchers with new opportunities to advance, monitor and evaluate sprint training.